Carbon Stock and Sink Economic Values of Forest Ecosystem in the Suwangi Island Nature Park, Tanah Bumbu Regency, South Kalimantan, Indonesia - Arfa Agustina Rezekiah; Abdi Fithria; Ahmad Yamani; Rosidah; Gt Syeransyah Rudy; Syam’ani D Ali; Yashinta Nur Shiba (Reinwardtia, 2026)
REZEKIAH, A. A., FITHRIA, A., YAMANI, A., ROSIDAH, RUDY, G. S., ALI, S. D. & SHIBA, Y. N. 2026. Carbon stock and carbon economic value of forest ecosystem in the Suwangi Island Nature Park, Tanah Bumbu Regency, South Kalimantan, Indonesia. Reinwardtia 25(1): 1‒11. — The forests on Suwangi Island are currently facing significant challenges arising from human activities, land degradation, and potential land-use conflicts, all of which critically undermine their capacity to absorb and store carbon. The purpose of this study was to analyze the carbon stock value and economic value of carbon stored in Suwangi Island Nature Park. The allometric method was employed to calculate carbon stocks, with sampling locations determined using purposive sampling. The carbon stock results were subsequently converted to estimate the economic value of carbon. The land cover types identified in Suwangi Island Nature Park include primary forest, secondary forest, plantation, medium-density mangrove forest, and high-density mangrove forest. The analysis revealed that the highest biomass was stored in the primary forest and the lowest in the medium-density mangrove forest. The total carbon that can be stored at the research site is 80,45554667 tons/ha, and the resulting carbon economic value is IDR 2,851,347,872.68. These findings highlight the significant variation in carbon storage across different land cover types and underscore the critical role of primary forests as major carbon sinks. The novelty of this study lies in the integration of spatial (ArcGIS), ecological (allometric), and economic approaches within a single analytical framework, which remains rarely applied. The practical implications of this research emphasize the importance of management strategies based on carbon economic valuation and the potential utilization of carbon trading schemes, such as REDD+, to enhance conservation incentives and ensure the sustainability of Suwangi Island Nature Park management.